Gestão da comunicação organizacional e práticas comunicativas na UFPB - Florêncio, Hannah Karollynne Barbosa (2022)
The management of organizational communication has been undergoing transformations as a result of information technologies, new models of administrative management and the demands of new configurations in inter-institutional relations with the market. These changes redesign the communication processes that assume a strategic character, focusing on the importance of institutional values and the alignment of the objectives that these organizations have with their administrative practices. When experiencing these processes, the Federal University of Paraíba (UFPB) needs a communication management that supports administrative management and establishes its institutional position vis-à-vis society. This research aimed to analyze the relationship between the dimensions of the Composite of Organizational Communication (OCC) and the communicative practices of the UFPB. The theoretical foundation was based on Kunsch (2003, 2006), which deals with the composite of integrated organizational communication; Torquato (2010), who brings the political dimension into organizational communication; Baldissera (2009, 2018), which addresses power relations from the perspective of organizational communication; Casali (2009) and Bueno (2003) who discuss the dimensions of communication in the public organizational context. The research is of an applied nature, inserted in a qualitative approach, with a descriptive character. Data collection was carried out through virtual questionnaires with professionals who work in sectors responsible for the management of communication in the centers, pro-rectories and supplementary bodies of the UFPB, in addition to the document analysis produced by the institution, (PDI 2019 - 2023), taking into account as a reference the dimensions of the composite of integrated organizational communication adapted for this study. Data analysis allowed us to propose guidelines and actions for the management of organizational communication at UFPB, involving details of the institution's communication principles and organizational restructuring of the Superintendence of Social Communication. To this end, it is proposed to map the professionals who work in the area of communication or similar in the institution by position and function, creation of working groups to discuss the propositions of the communication policy; creation of a training program for civil servants who will work with communication on UFPB campuses and units, among other actions.